Reserve currencies, problems and prospects of their development in the conditions of globalization and integration of banking systems - Xu, Jinming; Сюй Цзіньмін (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The work is devoted to the issues of reserve currency development and their future prospects in the context of globalization and integration of the banking system. The theoretical foundations of the international reserve currency system are considered, which play a vital role in maintaining financial stability and facilitating international trade and investment. The problems faced by the modern international reserve currency system in the context of global financial crises are summarized. The characteristics of the current international reserve currency system and the problems it faces are analyzed. The risks associated with a system dominated by a single currency, such as exchange rate fluctuations, monetary policy spillovers, and global financial stability problems, are summarized. Particular attention is paid to sharp fluctuations in exchange rates, which not only affect international trade and investment, but can also trigger financial crises, and the Trifin model is proposed, which aims to explore how to balance the supply and demand of reserve currencies in a diversified reserve currency system to achieve global financial stability.

Робота присвячена питанням розвитку резервних валют та їх майбутні перспективи в контексті глобалізації та інтеграції банківської системи. Розглядаються теоретичні основи міжнародної системи резервних валют, що відіграють життєво важливу роль у підтримці фінансової стабільності та сприянні міжнародній торгівлі та інвестиціям. Узагальнені проблеми, з якими стикається сучасна міжнародна резервна валютна система в контексті глобальних фінансових криз. Аналізуються характеристики поточної системи міжнародної резервної валюти та проблеми, з якими вона стикається. Узагальнено ризики, пов’язані з системою, де домінує одна валюта, такі як коливання обмінного курсу, перелив монетарної політики та проблеми глобальної фінансової стабільності. Особлива увага приділена різким коливанням обмінних курсів, які не тільки впливають на міжнародну торгівлю та інвестиції, а й можуть спровокувати фінансові кризи та запропоновано модель Тріфіна, яка має на меті дослідити, як збалансувати попит і пропозицію резервних валют у диверсифікованій резервній валютній системі для досягнення глобальної фінансової стабільності.
Резервні валюти, проблеми та перспективи їх розвитку в умовах глобалізації та інтеграції банківських систем
Scientific supervisor: Іващенко Марина Вікторівна, кандидат економічних наук, доцент кафедри фінансів, банківської справи та страхування
Keywords: SOCIAL SCIENCES::Business and economics::Business studies; globalization; integration of the banking system; development of reserve currencies; Triffin problem model; exchange rate fluctuations; multipolar model; internationalization of the renminbi; the stability of the international monetary system; глобалізація; інтеграція банківської системи; розвиток резервних валют; модель проблеми Тріфіна; коливання валютного курсу; багатополярна модель; інтернаціоналізація юаня; стабільність міжнародної валютної системи